2014
DOI: 10.5665/sleep.3310
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes of Adenotonsillectomy for Children with Obstructive Sleep Apnea: A Prospective Longitudinal Study

Abstract: Adenotonsillectomy leads to significant improvement in apnea-hypopnea index, though generally with incomplete resolution, but a worsening over time was observed in 68% of our cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 22 publications
1
102
0
1
Order By: Relevance
“…12 This study demonstrated that children in the early-adenotonsillectomy group had significant improvements in behavior, quality-oflife, and polysomnographic findings, and a significantly greater reduction in symptoms than the watchful-waiting group. However, in another study Huang et al 13 demonstrated that any initial improvements in OSA severity observed six months following adenotonsillectomy, were no longer present after 3 years in 67% of school-aged children. It remains unknown if similar to older children, the immediate benefits of adenotonsillectomy are the same for preschool-aged children and, if so, whether the benefits are still present in the longer term.…”
Section: Brief Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…12 This study demonstrated that children in the early-adenotonsillectomy group had significant improvements in behavior, quality-oflife, and polysomnographic findings, and a significantly greater reduction in symptoms than the watchful-waiting group. However, in another study Huang et al 13 demonstrated that any initial improvements in OSA severity observed six months following adenotonsillectomy, were no longer present after 3 years in 67% of school-aged children. It remains unknown if similar to older children, the immediate benefits of adenotonsillectomy are the same for preschool-aged children and, if so, whether the benefits are still present in the longer term.…”
Section: Brief Summarymentioning
confidence: 99%
“…OSA have included a wide age range, [9][10][11] older children, [12][13][14] or short follow-up periods of less than one year. 11,12,14,15 Similarly, the studies that have investigated the converse, i.e.…”
Section: Brief Summarymentioning
confidence: 99%
“…Most improvement in AHI occurs among children with an AHI >5 episodes·h −1 (class I and III) [126,211]. A class IV prospective, cohort study has provided evidence for potential OSAS recurrence within 3 years after adenotonsillectomy [212]. b) AHI >4.7 episodes·h −1 and obesity are significant risk factors for residual OSAS post-adenotonsillectomy (class I and IV, and meta-analysis) [126,156,213].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rate of obesity in our cohort was 16.5%, which is lower than some related US studies, but is similar to others. 27,34,35,40 This study has several limitations that may guide future prospective research. Above all, the decision to perform adenoidectomy or adenotonsillectomy depended on ENT and parental decision and not on designed randomization.…”
Section: Discussionmentioning
confidence: 99%